Techniques for cash management in scheduling manufacturing operations - Mehdy Morady Gohareh; Naser Shams Gharneh; Reza Ghasemy Yaghin (Journal of Industrial Engineering International, 2017)
The objective in traditional scheduling is usually time based. Minimizing the makespan, total flow times, total tardi costs, etc. are instances of these objectives. In manufacturing, processing each job entails a cost paying and price receiving. Thus, the objective should include some notion of managing the flow of cash. We have defined two new objectives: maximization of average and minimum available cash. For single machine scheduling, it is demonstrated that scheduling jobs in decreasing order of profit ratios maximizes the former and improves productivity. Moreover, scheduling jobs in increasing order of costs and breaking ties in decreasing order of prices maximizes the latter and creates protection against financial instability.
Keywords: 650; Scheduling; Single machine; Cash management; Cash deficiency; Manufacturing industries